Self-Instruction Training Untuk Meningkatkan Derajat Academic Buoyancy Mahasiswa - Wara Anggana; Sumedi P Nugraha; Ratna Syifa’a Rachmahana (Journal of Islamic and Contemporary Psychology (JICOP), 2022)
This study aims to determine the effect of self-instruction training interventions in increasing the level of student academic buoyancy. Students need to have a high level of academic buoyancy in order to be able to overcome daily academic challenges and overcome the decline in academic self-regulation (Martin & Marsh, 2009). Students who have a low or moderate degree of academic buoyancy will have obstacles in overcoming daily academic challenges and academic setbacks. This condition causes low academic achievement that students have. In order to overcome this problem, this research examines whether self-instruction training interventions with CBT can help students increase their degree of academic buoyancy. This self-instruction technique is a behavior modification technique that has two uses, namely improving maladaptive mindsets, becoming positive mindsets, which are then used to direct individuals by giving positive instructions to themselves to make behavior changes to become more adaptive (Meichenbaum, in Martin & Pear 2015). This study uses a single subject design with AB research pattern. The participant of this study was a male student at the Faculty of Medicine, with a moderate degree of academic buoyancy. The results of the study show that the self-instruction training technique can increase the degree of academic buoyancy.